Earth, Humankind, and the Haze Disaster - Pelupessy, Dicky (Journal of Delta Urbanism, 2025)
The Earth, Humans, and Haze Disaster was written in the wake of one of the worst forest fires that occurred in Indonesia. The essay refers to and highlights the book The Angry Earth by anthropologists Anthony Oliver-Smith and Susanna Hoffman, and the notion of disaster as the collapse of the cultural protection coined by Lowell Carr. It underlines an imbalance in the mutual relations between humans and the Earth. The haze disaster is not a result of an "angry Earth" but of human recklessness, systemic failure, and the erosion of preventive cultural structures. It is a warning that continues to be ignored, created by human action.